Mycobacterial Interspersed Repetitive Unit Can Predict Drug Resistance of Mycobacterium tuberculosis in China - Cheng, Xian-feng; Jiang, Chao; Zhang, Min; Xia, Dan; Chu, Li-li; Wen, Yu-feng; Zhu, Ming; Jiang, Yue-gen (Frontiers in Microbiology, 2016)
Background Recently, Mycobacterial Interspersed Repetitive Unit (MIRU) was supposed to be associated with drug resistance in M.tuberculosis (MTB). However, whether the MIRU was related to drug resistance actually was still unknown. This research was conducted to explore that association. Methods Drug susceptibility testing was used to evaluate the drug resistance of five anti-tuberculosis drug (isoniazid, INH; rifampicin, RFP; streptomycin, SM; ethambutol, EMB; and Paminosalicylicacid, PAS.). We tested the number of the repeat unite of MIRU (Mycobacterial Interspersed Repetitive Unit) locus based on PCR of miru-vntr genotyping. Then, through logistic regression, we evaluated the association between fifteen MIRU and the resistance. In addition, we explored the most suitable MIRU locus of identified MIRU loci for drug resistance through multivariate logistic regression. Results Among these fifteen MIRU, we found several MIRU loci could predict the drug resistance well. For example ,ETRB and ETRC could predict INH resistance; MIRU20 was associated with EMB resistance; and QUB11a was a predictive factor of PSA. Conclusion Our results may provide candidate regions for future genetic studies and aid in the prediction for drug resistance of MTB.